Media Pembelajaran Kimia menggunakan Mobile Learning berbasis Android - David David; Gusrio Tendra; Wilda Susanti; Gusrianty Gusrianty; Dwi Oktarina (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Chemistry is a relatively new material for Xth grade high school students, but many high school students still do not understand the basic concepts of chemistry and the lack of use of technology. The purpose of this research is to design and build learning media to make it easier for students to get to know chemistry using the Android platform. The method used in building this application is the SDLC (System Development Life Cycle) method, which starts by collecting data for system testing. Data collection was carried out around the Kalam Kudus Christian High School school environment in Pekanbaru with 40 students as research subjects. The system design is designed so that every high school student can use the application independently using a personal account. The tests used are black box testing and mean opinion score (MOS) testing. The result of black box testing is that the display or menu can run smoothly. while for MOS results, around 95% state that the application that was built gets very decent results from high school students. So that this application is used in accordance with the needs of high school students in helping to recognize basic chemical concepts.